The Italian economy - Zamagni, Vera 1943- (World economies, 2018)
The world's eighth largest economy has a unique shape and structure. Characterized by strong social networks and a niche capitalism built on successful small and medium-sized enterprises, the Italian economy has a nature distinct from its European neighbours. Vera Zamagni charts Italy's recent economic history from the postwar years of reconstruction through to the present day and the legacy of the financial crisis. Combining illustrative data with qualitative analysis, she provides a clear and rigorous presentation of the main features of the country's economy. The country's regional imbalances, political instability and corruption are situated alongside its strengths in social capital, its flourishing industrial districts and its high ranking in well-being indicators. Throughout, the contours of a much longer history are shown to have shaped the contemporary economy as much as recent trends, such as migration. The book provides a concise survey suitable for a range of introductory readerships seeking to understand the nature of recent Italian economic performance